Komunikasi Antarbudaya dalam Proses Adaptasi Pernikahan Multietnis Suku Jawa dan Suku Madura di Kabupaten Sidoarjo - Fanny Amelia Wati; Nikmah Suryandari (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
This study aims to understand the dynamics of intercultural communication in the adaptation process of interethnic marriages between Javanese and Madurese couples in Sidoarjo Regency, East Java. The primary focus is on how couples from different cultural backgrounds develop communication patterns and adjust to one another in their household life. This research employs a qualitative approach using a phenomenological design. Data were collected through in-depth interviews with three interethnic couples who have been married for more than two years. The findings reveal that communication within interethnic households is adaptive and context-dependent. Indonesian is predominantly used as the main language of interaction, serving as a neutral medium easily understood by both parties, while regional languages are preserved for specific cultural situations. Challenges in communication arise from differences in emotional expression and communication styles, which often lead to misunderstandings, especially during the early stages of marriage. However, couples who engage in open and respectful communication are able to overcome these differences and create a harmonious relationship. Cultural adaptation is also reflected in parenting practices, division of household roles, and interactions with extended families. Support from extended families significantly contributes to the process of cultural acceptance. In conclusion, interethnic marriages between Javanese and Madurese couples represent an ongoing negotiation of values and the formation of a new, inclusive family identity through mutual understanding and culturally respectful communication.